2022
DOI: 10.1002/hbm.26085
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous brain activity abnormalities in migraine: A meta‐analysis of functional neuroimaging

Abstract: Neuroimaging studies have demonstrated that migraine is accompanied by spontaneous brain activity alterations in specific regions. However, these findings are inconsistent, thus hindering our understanding of the potential neuropathology. Hence, we performed a quantitative whole‐brain meta‐analysis of relevant resting‐state functional imaging studies to identify brain regions consistently involved in migraine. A systematic search of studies that investigated the differences in spontaneous brain activity patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 80 publications
2
13
0
Order By: Relevance
“…Moreover, the abnormal activity in MFG was negatively correlated with the pain intensity of migraine attacks (Russo et al, 2012). The abnormal neural activity of the IFGtriang was also detected in migraine patients (Cai et al, 2022; Yang et al, 2022). The PreCG is an important part of the frontal lobe, which was found abnormality in migraine patients and is related to pain processing and modulation (Androulakis et al, 2018; Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, the abnormal activity in MFG was negatively correlated with the pain intensity of migraine attacks (Russo et al, 2012). The abnormal neural activity of the IFGtriang was also detected in migraine patients (Cai et al, 2022; Yang et al, 2022). The PreCG is an important part of the frontal lobe, which was found abnormality in migraine patients and is related to pain processing and modulation (Androulakis et al, 2018; Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…According to a prior study, the frequency of headache attacks (days of attacks/month) in migraine patients significantly influences the activation magnitude of the THA.L (Russo et al, 2014). And headache severity in migraine patients was positively associated with brain activity in the THA.L (Cai et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ReHo is specialized in explore local connectivity in a specific region by characterizing its relationship with nearby voxels in a specific region ( 59 ). Meta-regression analysis has indicated that migraine patients' visual analog scale score was associated with increased brain activity in the left thalamus ( 20 ). Using different meta-analysis method and sensitivity analysis, we also concluded that the left thalamus and brainstem of migraine patients were more spontaneous activated than HCs.…”
Section: Discussionmentioning
confidence: 99%
“…If there are regions that both function and structure altered in migraine patients. Based on ReHo, amplitude low-frequency fluctuation (ALFF) and positron emission tomography (PET), meta-analysis demonstrated decreased activity in the angular gyrus, visual cortex, and cerebellum, while increased in the caudate, thalamus, pons, and prefrontal cortex ( 20 ). On the other hand, GMV decrease in posterior insular-opercular regions, the bilateral prefrontal cortex, and the anterior cingulate cortex were revealed with AES-SDM ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%